A 3.16–7 GHz transformer-based dual-band CMOS VCO*Project supported by the National High Technology Research and Development Program of China (No. 2011AA10305) and the National Natural Science Foundation of China (No. 60901012). (March 2015) - Li, Zhu; Wang, Zhigong; Li, Zhiqun; Li, Qin; Liu, Faen
Abstract A dual-band, wide tuning range voltage-controlled oscillator that uses transformer-based fourth-order (LC) resonator with a compact common-centric layout is presented. Compared with the traditional wide band (VCO), it can double frequency tuning range without degrading phase noise performance. The relationship between the coupling coefficient of the transformer, selection of frequency bands, and the quality factor at each band is investigated. The transformer used in the resonator is a circular asymmetric concentric topology. Compared with conventional octagon spirals, the proposed circular asymmetric concentric transformer results in a higher quality-factor, and hence a lower oscillator phase noise. The VCO is designed and fabricated in a 0.18-μm CMOS technology and has 75% wide tuning range of 3.16–7.01 GHz. Depending on the oscillation frequency, the VCO current consumption is adjusted from 4.9 to 6.3 mA. The measured phase noises at 1 MHz offset from carrier frequencies of 3.1, 4.5, 5.1, and 6.6 GHz are −122.5, −113.3, −110.1, and −116.8 dBc/Hz, respectively. The chip area, including the pads, is 1.2 × 0.62 mm2 and the supply voltage is 1.8 V.